(untitled) (ModaPalavra e-periódico, 2019)
Based on the Brazilian feature film Neon Bull (2015), directed by GabrielMascaro, the present article aims to understand the dimensions of the identity of thecontemporary subject, through the character Iremar. Thus, a discussion is openedbetween the contemporary, the sensitive and the fashion, under the interpretations ofthe authors Giorgio Agamben and Emanuele Coccia. The result of theresearchcomes from the concepts and the microanalysis of four scenes examined throughthe methodology of filmic analysis of the image, according to Jacques Aumont andMichel Marie. It was possible to verify that the narrative of the work in analysis in thereferring one to the contemporary world, the sensations and ruptures of stereotypesand paradigms.